Influence of the synthesis conditions on the characteristics and metal adsorption properties of the 3-(1,4-phenylenediamine)propylsilica xerogel - J. C. P. Vaghetti; J. L. Brasil; T. M. H. Costa; E. C. Lima; E. V. Benvenutti (Eclética Química, 2018)
The hybrid 3-(1,4-phenylenediamine)propylsilica xerogel was obtained starting from two different organic precursor quantity (5 and 8 mmol) to 22 mmol of TEOS, in the synthesis. The xerogel samples were characterized by using CHN elemental analysis, N 2 adsorption-desorption isotherms, infrared thermal analysis. The xerogel was used as metal sorbent for Cu 2+ , Cd 2+ and Pb 2+ in aqueous solution with concentration range of 10 -3 to 10 -5 mmol l -1 . The quantity of organic precursor added in the synthesis influences the characteristics of the xerogel as morphology and thermal stability, as well as the metal adsorption capacity.